Evaluation of the ferromagnetic particle content and defect detection in multifunctional fiber composites through nondestructive techniques - Ganslmaier, Josef; Littig, Marcel; Santl, Dominik; Bleckmann, Matthias; Höfer, Philipp (Optical engineering, 2025)
Functionalizing polymers by adding micro- or nanoparticles presents a method to adjust specific material properties, such as electromagnetic characteristics or thermal conductivity. To ensure excellent mechanical properties in addition to functionalization, the particles can be integrated into short and continuously fiber-reinforced plastics (FRP). One possible approach is to apply the particles during the fabrication process of the continuous FRP semi-finished products. Consequently, exact monitoring of material components presents a considerable challenge from supervision during manufacturing to quality control of in-service components. This study explores the potential of several well-established nondestructive evaluation methods regarding their applicability to defect detection and quantification of the particle volume fraction and distribution within the composite. For the first test objective, carbonyl iron-filled FRP samples of two different particle contents are manufactured. PTFE sheets of different sizes are placed within the laminate to simulate delamination defects. For filler content evaluation, samples of an epoxy matrix and carbonyl iron particles with a volume fraction ranging from 0 to 50 vol.% are produced. The test subjects are analyzed using ultrasonic testing, X-ray computed tomography, thermography, and electromagnetic tests. The study aims to give an overview of the changed characteristics and limitations that particle functionalized composites pose on each of the presented methods. Furthermore, the findings in this study demonstrate the possibility for nondestructive evaluation of ferromagnetic filler contents within multimaterial composites through the utilization of their magnetic properties.